Mewujudkan Karakter Murid Rabbani Melalui Program Ramadhan Mengaji di SMA 09 Kota Makassar - Saifuddin, Saifuddin; Mario, Mario; Wahda, Muhammad Aksa; Amandaria, Riri; Amirullah, Amirullah (Humanis, 2025)
This program aims to instill and develop good values in order to humanize humans, to improve character and train the intellectuals of students, and also to create a knowledgeable generation with character that can provide benefits to the surrounding environment. The important points taught to students are: (1) Education of faith/belief; to produce a young generation of the future who are strong in imtaq. (2) Education of worship; to be taught to children in order to create a young generation who have commitment and are accustomed to carrying out worship, such as praying, fasting, and reading the Koran. (3) Education of akhlakul karimah; to produce a rabbani generation, or a generation that is pious, intelligent and has noble morals. The methods used in this activity are lecture and practice methods. This activity takes place for 7 days during the month of Ramadan at SMA 09 Makassar City. The results of the activity show the high spirit and enthusiasm of students in following the entire series of learning until the end of the Ramadhan Mengaji Program. Through the method of practicing ablution, praying, and reading the Quran, students can strengthen their faith and have Islamic morals among other students. Abstract. Program ini bertujuan menanamkan dan m